1989
DOI: 10.1902/jop.1989.60.4.205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Concentrations of Collagen Barrier on Periodontal Wound Healing

Abstract: Collagen membrane preparations were manufactured with the aim of enhancing wound healing following periodontal surgery. In order to clarify effects of different concentrations of collagen on wound healing, a basic study was performed. Solutions containing 0.5%, 1.0%, and 1.3% atelocollagen were treated with hexamethylenediisocyanate (HMDIC) for cross-linking, and collagen membranes were prepared with each solution. Periodontal flap surgery was performed on the palatal gingiva beside the maxillary first molar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…For resorbable membranes, especially membranes made from collagen, primary closure, while still being favorable, seems not to be a critical for success anymore. Since fi broblasts from the wound margins are able to attach to the membrane, 10 while the proliferation of epithelial cells is stopped in the presence of collagen, 39 the defect is quickly sealed off from the oral fl ora by connective tissue becoming epithelialized. However, collagen membranes seem to disintegrate at a high rate when exposed to the oral environment 40 owing to collagenases produced by several oral bacteria, including Porphyromonas gingivalis and Bacteroides melaninogenicus.…”
Section: Cells Used For In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For resorbable membranes, especially membranes made from collagen, primary closure, while still being favorable, seems not to be a critical for success anymore. Since fi broblasts from the wound margins are able to attach to the membrane, 10 while the proliferation of epithelial cells is stopped in the presence of collagen, 39 the defect is quickly sealed off from the oral fl ora by connective tissue becoming epithelialized. However, collagen membranes seem to disintegrate at a high rate when exposed to the oral environment 40 owing to collagenases produced by several oral bacteria, including Porphyromonas gingivalis and Bacteroides melaninogenicus.…”
Section: Cells Used For In Vitro Studiesmentioning
confidence: 99%
“…Therefore, several other techniques to cross-link collagen have been described. 10,11 Many different collagen barrier devices are on the market or under development today (Table 1). In addition to the effects of cross-linking, it has been shown that the surface topography of a membrane 12 and the origin of the collagen used [13][14][15] may affect the properties of a GTR or GBR membrane.…”
Section: Introductionmentioning
confidence: 99%
“…70 Interesting as this approach may be, no information is available on the actual binding of collagen solution, which incidentally gels at body temperature, to the root surface and its fate. Since complete periodontal therapy usually involves more than one area of surgery, the possibilities of subjects developing host responses following repeated use of collagen need consideration.…”
Section: Regeneration Of Connective Tissue Attachment To Previousmentioning
confidence: 99%
“…Thus, the effectiveness of the collagen membrane was debated in regeneration literature because of its relatively fast resorption rate even after cross-linking. However, recently reported evidence suggested that since the epithelial proliferation occurs within the first 14 days of periodontal wound healing, it is postulated that the period of time in which a collagen membrane remains intact is sufficient to inhibit epithelial migration (19,21).…”
Section: Bioabsorbable Barrier Membranesmentioning
confidence: 99%